Penggunaan Google Sites dalam Mengembangkan Akhlak Siswa Sekolah Dasar - Riska Putri Wulandani; Melisa Putri Siti Zahrani; Faras Julian Yasykur; Ani Nur Aeni (Journal on Education, 2023)
This research explores the Google Sites platform as an effective and efficient learning medium for developing students. This research was conducted using the Design and Development (D&D) approach, with a series of studies on the process of analysis, design, development and implementation. Data were obtained through instruments in the form of field documentation and questionnaires or questionnaires which were distributed to teachers of Islamic religious education in elementary schools and high school students in elementary schools. Data processing is done quantitatively. The data shows that Google Sites as a digital media for learning PAI in elementary schools is quite easy in delivering learning because there are interactive animated powerpoint videos in which there are animated characters, there are songs about noble characters in them, so that learning activities are more attractive to students' learning motivation. When watching animated learning videos, most students feel happy.